Peritoneal interleukin-6 and tumor necrosis factor-alpha as markers for early detection of anastomotic dehiscence following surgery for colorectal cancer - Ladika-Davidović, Blaženka (Array, 2019)
Anastomotic dehiscence is one of the most serious complications following surgery for colorectal cancer, and early detection of anastomotic dehiscence is critical to minimize mortality and morbidity. The aim of this study was to determine the value of peritoneal interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) as markers for preclinical detection of anastomosis dehiscence following colorectal surgery. Concentrations of IL-6 and TNF-α were measured in drain fluid obtained from 58 patients on days 1 to 4 following surgery for colorectal cancer. Five out of 58 patients developed anastomosis dehiscence. Patients who developed anastomosis dehiscence had significantly higher concentration of IL-6 on day 1 after surgery, and TNF-α on day 1, 2 and 4 after surgery. Interleukin-6 on day 1 was predictive for anastomosis dehiscence with specificity of 83%, sensitivity of 80%, positive predictive value (PPV) of 31% and negative predictive value (NPV) of 98%. TNF-α was predictive for anastomosis dehiscence on day 1 (specificity 92%, sensitivity 80%, PPV 50%, NPV 98%), day 2 (specificity 94%, sensitivity 80%, PPV 57%, NPV 98%), and day 4 (specificity 83%, sensitivity 100%, PPV 27%, NPV 100%). Our study indicates the potential use of peritoneal cytokines IL-6 and TNF-α as additional diagnostic tool for early detection of anastomosis dehiscence following colorectal surgery.